The Impact of Anticoagulation on Trauma Outcomes: An National Trauma Data Bank Study. Issue 7 (July 2020) - Nguyen, Rosalynn K.; Rizor, James H.; Damiani, Michael P.; Powers, Andrew J.; Fagnani, Jacob T.; Monie, Daphne L.; Cooper, Shelby S.; Griffiths, Andrew D.; Hellenthal, Nicholas J.
Background: Increased prevalence of patients on anticoagulants and the advent of new therapies raise concern over how these patients fare if they sustain a traumatic injury. We investigated the role of prehospitalization anticoagulation therapy in trauma-related mortality and postacute disposition. Methods: A retrospective analysis was performed on patients who sustained traumatic injury identified in the 2017 National Trauma Data Bank (NTDB). Patients with and without anticoagulation therapy were analyzed to identify differences in demographics, injury type, Injury Severity Score (ISS), and trauma outcomes including hospital length of stay, ER, final hospital disposition, and mortality. Logistic regression was used to correlate anticoagulation to mortality and facility discharge. Results: Of the 1 000 596 patients included, 73 602 (7%) patients were on anticoagulants at the time of their trauma. Increased age was the strongest predictor for anticoagulation therapy (odds ratio 5.54, 95% CI 5.44-5.63), but being female and white were also independent predictors of anticoagulation ( P < .001). Patients on anticoagulants had a significantly longer length of stay (5.11 days; 95% CI 5.06-5.15) than those who were not (4.37 days, 95% CI 4.36-4.39), were 2.20 times more likely to die (95% CI 2.12-2.28, P < .001), and were 2.77 times more likely to be discharged to a facility (95% CI 2.73-2.81, P < .001). Anticoagulation remained a significant predictor of worse trauma outcomes even when accounting for age and ISS in multivariate analysis. Discussion: Anticoagulation preceding trauma-related admission is associated with higher mortality and an increased likelihood of the need for a posthospital care facility.